Phenotypic characteristics of environmental Pseudomonas aeruginosa: an in vitro study on epidemiological aspects - Gajdács, Márió; Urbán, Edit; Pallós, Péter; Márta, Adrienn; Matusovits, Danica; Kárpáti, Krisztina; Battah, Basem; Hetta, Helal F.; Khusro, Ameer; Dordevic, Dani; Kushkevych, Ivan (Acta Biologica Szegediensis, 2023)
Pseudomonas aeruginosa is one of the most commonly isolated species among non-fermenting Gram-negative bacteria, both from clinical samples and from environmental sources. The survival of the species in harsh conditions is ensured by the production of a protective biofilm; assessment of biofilm-forming capacity aids future pathogen eradication strategies. The aim of our present study was to assess the relationship between antibiotic resistance, biofilm-forming capacity and other phenotypic virulence factors in environmental P. aeruginosa isolates. One hundred and fourteen (n = 114) isolates were included in the study, which were obtained from various geographical regions and environmental origins. Antimicrobial susceptibility testing was carried out using standard protocols. Biofilm-forming capacity and pyocyanin pigment production were tested using microtiter plate-based methods. Swarming, swimming and twitching motility, and siderophore-production were assessed using agar-plate based methodologies. Resistance in environmental isolates were highest for levofloxacin/ciprofloxacin 49.12% (n = 56), ceftazidime 42.98% (n = 49) and cefepime 35.96% (n = 41), while lowest for colistin 0% (n = 0); overexpression of RND-type efflux pumps was seen in 33.33% (n = 33) of isolates. 21.93% (n = 25) met the criteria to be classified as multidrug resistant (MDR). 17.54% (n = 20) of isolates were weak/non-biofilm producers, while (25.45%, n = 29) and (57.01%, n = 65) were moderate and strong biofilm producers, respectively. No significant differences were noted in biofilm-formation (OD570 values non-MDR [mean ± SD]: 0.396 ± 0.138 vs. MDR: 0.348 ± 0.181; p > 0.05) or pyocyanin pigment production (OD686 values non-MDR: 0.403 ± 0.169 vs. MDR: 0.484 ± 0.125; p > 0.05) between MDR and non-MDR environmental P. aeruginosa. Highest motility values were observed for swarming motility, followed by swimming and twitching motility; no relevant differences (p > 0.05) in motility were noted in the context of MDR status or biofilm-formation in the tested isolates. P. aeruginosa is an opportunistic pathogen with high medical importance, being a causative agent of recalcitrant infections, which are becoming difficult to treat with the onset of MDR. Further studies are warranted to assess biofilm-forming capacity, and to provide insights into the mechanisms underlying biofilm-formation both in isolates of clinical and environmental origins.